TUMBUHAN YANG DIKUNJUNGI LEBAH PEKERJA Apis dorsata Fabr (HYMENOPTERA: APIDAE) DI PALANGKI KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG - Yawati, Septri; Jasmi, Jasmi; Rizki, Rizki (STKIP PGRI Sumbar, 2013)
ABSTRACTApis dorsata Fabr is one of the insects that benefit humans , especially itcan produce honey . Honey bee colony consists of a queen bee , drones and bees worker. Apis dorsata in life is influenced by the environment one food source availability . Related with that have done research on the plant visit Apis dorsata Fabr bees worker ( Hymenoptera : Apidae ) in Palangki Kecamatan IV Kabupaten Sijunjung on April 2013 with the aim to determine which plants visited by bees Apis dorsata Fabr workers in Palangki Kecamatan IV Nagari Kabupaten Sijunjung . This study uses direct observation of plants visited by bees field workers . The study was conducted one month , once a week starting from 06.00 until 18.00 with a distance of 500 meters from the tree where the colony of Apis dorsata . From the results of research on plant visit Apis dorsata Fabr bees worker ( Hymenoptera : Apidae ) in Palangki Kecamatan IV Nagari Kabupaten Sijunjung within a radius of 500 meters to 30 species and 16 familia . Familia is most commonly found in plants visited Apis dorsata Fabr bees worker ( Hymenoptera : Apidae ) in Palangki Kecamatan IV Nagari Kabupaten Sijunjung familia Leguminoceae is composed of nine species.